Digital Tools for Qualitative Research: Disruptions and Entanglements. (December 2017) - Paulus, Trena M.; Jackson, Kristi; Davidson, Judith
In this introduction to the special issue on digital tools for qualitative research, we focus on the intersection of new technologies and methods of inquiry, particularly as this pertains to educating the next generation of scholars. Selected papers from the 2015 International Congress of Qualitative Inquiry special strand on digital tools for qualitative research are brought together here to explore, among other things, blogging as a tool for meaning-making, social media as a data source, data analysis software for engaging in postmodern pastiche and for supporting complex teams, cell phone application design to optimize data collection, and lessons from interactive digital art that pertain to the use of digital tools in qualitative research. This collection disrupts common conceptions (and persistent misconceptions) about the relationship between digital tools and qualitative research and illustrates the entanglements that occur whenever humans intersect with the nonhuman, the human-made, or other humans.